Zika Virus Non-Structural Protein NS5 Inhibits the RIG-I Pathway and Interferon Lambda 1 Promoter Activation by Targeting IKK Epsilon - Lundberg R.; Melén K.; Westenius V.; Jiang M.; Österlund P.; Khan H.; Vapalahti O.; Julkunen I.; Kakkola L. (MDPI, 2022)
The Zika virus (ZIKV) is a member of the Flaviviridae family and an important human pathogen. Most pathogenic viruses encode proteins that interfere with the activation of host innate immune responses. Like other flaviviruses, ZIKV interferes with the expression of interferon (IFN) genes and inhibits IFN-induced antiviral responses. ZIKV infects through epithelial barriers where IFN-lambda 1 is an important antiviral molecule. In this study, we analyzed the effects of ZIKV proteins on the activation of IFN-lambda 1 promoter. All ZIKV proteins were cloned and transiently expressed. ZIKV NS5, but no other ZIKV protein, was able to interfere with the RIG-I signaling pathway. This inhibition took place upstream of interferon regulatory factor 3 (IRF3) resulting in reduced phosphorylation of IRF3 and reduced activation of IFN-lambda 1 promoter. Furthermore, we showed that ZIKV NS5 interacts with the protein kinase IKK epsilon, which is likely critical to the observed inhibition of phosphorylation of IRF3.